(untitled) (Cardiovascular Journal, 2015)
Background: Acute coronary syndrome is a cardiac emergency. It is increasingly common in younger peoples. Management of elderly peoples is difficult due to their associated comorbidity. This study tried to compare the in-hospital outcome of the younger and older patients with acute coronary syndrome. Methods: The study was a comparative cross sectional study. Clinical and biochemical evaluation was done in hospital settings. A total number of 120 patients were included in the study and divided into two groups according to distribution of age. In group I there were elderly groups of aged >60 yrs. and in group II there were patients within the age 40 to 60 yrs. All the data were collected systematically in a preformed data collection form. Results: Group I populations had more in hospital stay and more complications than group II. Conclusion: The study revealed significant association with age and outcome of Acute coronary syndrome patients. Complications of acute coronary syndrome increase as the age of the patients increases. Cardiovasc. j. 2015; 8(1): 49-52